2018
DOI: 10.1111/gcbb.12571
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic covariations of traits underlying sorghum stem biomass production and quality and their regulations by water availability: Insight from studies at organ and tissue levels

Abstract: Sweet and biomass sorghum are expected to contribute increasingly to bioenergy production. Better understanding the impacts of the genotypic and environmental variabilities on biomass component traits and their properties is essential to optimize energy yields. This study aimed to evaluate whether traits contributing to stem biomass growth and biochemical composition at different biological scales (co)vary with the genotype and the water status in sorghum. Height genotypes were studied over two years in field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
3
5
0
Order By: Relevance
“…We showed that most of the biochemical traits were impacted by the NI scenario in both years. These findings have already been reported in maize (El Hage et al, 2018;Virlouvet et al, 2019), sorghum (Luquet et al, 2019), and miscanthus (Van Der Weijde et al, 2017). Nevertheless, what is striking in the present analysis is that even if rainwater was supplied in large quantities from the onset of the stress period and of the development of the internode below the ear in 2015, biochemistry traits (such as PCAest and lignin contents) and in vitro digestibilities of the internodes were impacted similarly in 2014 and 2015, while the histological traits were not.…”
Section: Responses To Water Deficit Are Different When Considering Bisupporting
confidence: 85%
“…We showed that most of the biochemical traits were impacted by the NI scenario in both years. These findings have already been reported in maize (El Hage et al, 2018;Virlouvet et al, 2019), sorghum (Luquet et al, 2019), and miscanthus (Van Der Weijde et al, 2017). Nevertheless, what is striking in the present analysis is that even if rainwater was supplied in large quantities from the onset of the stress period and of the development of the internode below the ear in 2015, biochemistry traits (such as PCAest and lignin contents) and in vitro digestibilities of the internodes were impacted similarly in 2014 and 2015, while the histological traits were not.…”
Section: Responses To Water Deficit Are Different When Considering Bisupporting
confidence: 85%
“…Moderate to high broad sense heritability associated with genetic coefficients of variation over 10% was observed for all the histological traits These results confirm the detection of significant genotype effects in previous studies performed by Perrier et al, (2017) and Luquet et al, (2019) on narrower panels of genotypes (2 and 8, respectively). Although histological analyses were only performed on one site over 3 years, questioning the existence of genotype by site interactions, the medium to high inter‐year correlations observed combined with the weak effects of genotype by year and genotype by water availability treatments reported by Luquet et al, (2019, see their Table 5) suggest a relatively stable ranking of the genotypes across environmental conditions. Broad sense heritability observed for the outer Z1 region area roughly corresponds with the repeatability reported by Gomez et al, (2018) on sorghum for their “rind area” trait (0.72).…”
Section: Discussionsupporting
confidence: 90%
“…Although functional validation is the gold standard toward the validation of gene function, complementary approaches are also relevant to improve the identification of the most relevant genes to use in future breeding schemes. Assessment of the expression differences of genotypes harboring different patterns of accumulation Luquet et al, 2019) and in different environmental conditions (Perrier et al, 2017;Luquet et al, 2019;Virlouvet et al, 2019) would probably allow to refine our choices to maximize their transposition to breeding programs in the future. In addition, it would be interesting to increase the resolution of the transcriptomic analyses through the analysis of expression of specific groups of cells (e.g., parenchyma vs. vascular bundles.…”
Section: Resultsmentioning
confidence: 99%